Virulence Structure of the Wheat Powdery Mildew Population in Serbia - Mirjana Lalošević; Radivoje Jevtić; Vesna Župunski; Stevan Maširević; Branka Orbović (Agronomy, 2021)
Powdery mildew is a common, economically important disease in the wheat growing area of Serbia. A large-scale virulence survey of its causal agent Blumeria graminis f. sp. tritici population was performed in the period 1995–2013. A total of 1013 isolates were recovered from the collected chasmothecial samples. Among them, 862 unique pathotypes were identified using a differential set of 20 wheat lines with known powdery mildew (Pm) resistant genes. The pathogen was highly diverse. Number of virulence genes (virulence complexity) per isolate was large, supporting a constant need to extend the differential set of wheat with newly identified Pm genes. Virulence frequencies to Pm6, Pm7, and Pm5+8 were high throughout the 19-year period, in contrast with that to Pm5+6, which was consistently at a low level. The most significant change in the population was observed for virulence to the Pm2+4b+6 gene combination, with an increasing frequency of virulence to this gene combination over the years. High virulence complexity and genetic diversity of the population are the most influential factors for the damaging epidemics that this pathogen can cause.